Not sure about 1 and 8, I think there trapezoids but not sure.
2 is a square
3 is a rectangle
4 and 10 are a rhombus
5 and 11 are parallelograms
6 is a kite
7 is a square
can't really see 9
can't really see 12
Hope that helped.
Answer: x = -5
Step-by-step explanation:
1) subtract 4 from both sides (-5x = 25)
2) divide -5 from both sides (x = -5)
Then you have the answer!
The answer is: 45 * 10 ⁻¹¹ .
___________________________________________
Explanation:
____________________________________________
Given: (9 * 10⁻⁵) * (5 *10 ⁻⁶) ; Simplify.
____________________________________________
(9 * 10⁻⁵) * (5 *10⁻⁶) =
9 * 5 * 10⁻⁵ * 10⁻⁶ =
(9 * 5) * 10⁻⁵ * 10⁻⁶
45 * 10⁻⁵ * 10⁻⁶ ;
______________________________________
Note the following property of exponents:
xᵃ * xᵇ = x⁽ᵃ⁺ᵇ⁾ ;
As such, 10⁻⁵ * 10⁻⁶ = 10⁽⁻⁵ ⁺ ⁻⁶) = 10 ⁻¹¹ ;
______________________________________
So; 45 * 10⁻⁵ * 10⁻⁶
= 45 * 10⁻¹¹ .
______________________________________
If I've read this correctly, it looks like this.
![\dfrac{(x + 1)}{2 - \dfrac{(x + 2)}{3x}}](https://tex.z-dn.net/?f=%20%5Cdfrac%7B%28x%20%2B%201%29%7D%7B2%20-%20%5Cdfrac%7B%28x%20%2B%202%29%7D%7B3x%7D%7D%20%20%20)
If that is correct, then the first step is to put the top part of the denominator over 3x
The next part is to flip a three tier fraction. I'm afraid I have to show what happens. My latex is not that strong.
What you get is
![\dfrac{3x*(x + 1)}{(5x - 2)}](https://tex.z-dn.net/?f=%20%5Cdfrac%7B3x%2A%28x%20%2B%201%29%7D%7B%285x%20-%202%29%7D%20%20)
This is just about your final answer. You could write it as
![\dfrac{3x^2 + 3x}{(5x - 2)}](https://tex.z-dn.net/?f=%20%20%5Cdfrac%7B3x%5E2%20%2B%203x%7D%7B%285x%20-%202%29%7D%20%20)